Upregulation of neuropeptide Y in cardiac sympathetic nerves induces stress (Takotsubo) cardiomyopathy - Arai, Takahide; Kanazawa, Hideaki; Kimura, Kensuke; Munakata, Masahito; Yamakawa, Hiroyuki; Shinmura, Ken; Yuasa, Shinsuke; Sano, Motoaki; Fukuda, Keiichi (Frontiers in Neuroscience, 2022)
Substantial emotional or physical stress may lead to an imbalance in the brain, resulting in stress cardiomyopathy (SC) and transient left ventricular (LV) apical ballooning. Even though these conditions are severe, their precise underlying mechanisms remain unclear. Appropriate animal models are needed to elucidate the precise mechanisms. In this study, we established a new animal model of epilepsy-induced SC. The SC model showed an increased expression of the acute phase reaction protein, c-Fos, in the paraventricular hypothalamic nucleus (PVN), which is the sympathetic nerve center of the brain. Furthermore, we observed a significant upregulation of neuropeptide Y (NPY) expression in the left stellate ganglion (SG) and cardiac sympathetic nerves. NPY showed neither positive nor negative inotropic and chronotropic effects. On the contrary, NPY could interrupt β-adrenergic signaling in cardiomyocytes when exposure to NPY precedes exposure to noradrenaline. Moreover, its elimination in the left SG via siRNA treatment tended to reduce the incidence of SC. Thus, our results indicated that upstream sympathetic activation induced significant upregulation of NPY in the left SG and cardiac sympathetic nerves, resulting in cardiac dysfunctions like SC.